Impact of the changing area sown to winter wheat on crop water footprint in the North China Plain. (October 2015) - Wang, Xue; Li, Xiubin; Fischer, Günther; Sun, Laixiang; Tan, Minghong; Xin, Liangjie; Liang, Zhuoran
Highlights: About a half of water uses for winter wheat are met by rainfall in the south, compared to a third in northern NCP. A north–south shift of area sown to winter wheat was identified in the NCP during 1998–2011. The shift of area resulted in decreased use of groundwater for winter wheat in the NCP. The shift of area also resulted in increased proportion of green water in total water use in the NCP. Large savings were made in the amount of irrigation water used for winter wheat in the Hebei Plain. Abstract: The serious water scarcity and groundwater over-exploitation problems of the North China Plain (NCP) have aroused worldwide concerns. Achieving a reduction in agricultural water use is critical, because agriculture is the largest water consumer in the NCP. New solutions to these problems may lie in changes in the area sown to winter wheat across the NCP. In this study, the water footprint ( WF ) was applied as an aggregative indicator to evaluate the impact of the changing area sown to winter wheat. A Chinese version of the AEZ model, the China-AEZ model, was used for the evaluation. The results showed: (1) Green water plays a more significant role in winter wheat production in the southern part of the NCP than in the north; about a half of the water requirements for winter wheat are met by green water in the southern part of the NCP, compared to only a third in the north. (2) As a result of the north–south shift in the area sown to winter wheat during the period 1998–2011, the WF, the green water footprint ( WF green ) and the surface water footprint ( W F b l u e s ) for winter wheat increased, respectively, by 459 × 10 6  m 3  yr −1 (0.9%), by 973 × 10 6  m 3  yr −1 (4.2%) and by 47 × 10 6  m 3  yr −1 (0.5%), whereas the groundwater footprint ( W F b l u e g ) diminished by 561 × 10 6  m 3  yr −1 (3.4%). The contribution of green water also increased, from 46.3% in 1998 to 47.8% in 2011, concurrent with the changes in the area sown to winter wheat. (3) The Hebei Plain, in the northern part of the NCP, conserved 1856 × 10 6  m 3  yr −1 of blue water footprint ( WF blue ) for winter wheat during the period 1998–2011, equivalent to about one third of the total amount of water supplied by the Middle Route of the South-to-North Water Transfer Project (MRP) in 2010. By comparison, WF and its components all increased in the southern provinces of the NCP. The diminishing requirement for groundwater and the increasing role of green water in winter wheat production encourage policies aimed at the further optimization of agricultural land use and the achievement of integrated blue-green water management in the NCP.